Gross, Radiographic and Computed Tomographic Study of the Cranial Cavity Nasal Cavity, Dentition and Sinuses of the Local Pig (Zovawk) of Mizoram - Choudhary, O.P. (Indian Journal of Veterinary Anatomy, 2020)
on the cranial cavity, nasal cavity, dentition and sinuses of the local pig of Mizoram. The roof of the cranial cavity was formed by frontal, parietal and interparietal bones and the lateral wall of the cranial cavity was formed by frontal, parietal and temporal bones. The cranial wall was formed by the cribriform plate of the ethmoid, which separates the cranial cavity with the nasal cavity. The caudal wall of the cranial cavity was formed by the occipital bone and terminated as large foramen magnum. The nasal cavity was a cone-shapedlongitudinal passage which extended through the upper part of the face and divided into right and left halves by a median nasal septum. The lateral wall of the nasal cavity was formed by the maxilla, premaxilla and perpendicularpart of the palatine bones. In the present study, the skull of the Zovawk consisted of six incisors, two canines, eight premolar and six molar teeth on the upper and lower jaw. In the present study, the paranasal sinuses wereseparated into two main complexes (maxillary and frontal) and two small sinuses (sphenoid and lacrimal), which were clearly visible in the computed tomographic scan.